2010
DOI: 10.1098/rsta.2010.0094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fatigue on the simulated relation between the amplitude of the surface electromyogram and muscle force

Abstract: A linear relation between surface electromyogram (EMG) amplitude and muscle force is often assumed and used to estimate the contributions of selected muscles to various tasks. In the presence of muscle fatigue, however, changes in the properties of muscle fibre action potentials and motor unit twitch forces can alter the relation between surface EMG amplitude and force. A novel integrative model of motor neuron control and the generation of muscle fibre action potentials was used to simulate surface EMG signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 43 publications
2
56
0
1
Order By: Relevance
“…In contrast, the rate of decline in maximal torque during 5 sets of 30 repetitions with maximal lengthening contractions with the ankle dorsiflexor muscles was greater for old adults (Baudry et al, 2007). (Dideriksen et al 2010b). One protocol (top) involved simulating contractions at five submaximal target forces (20,35,50,65, and 85% of MVC force) beyond the point in time when the muscle can achieve the target force and both EMG amplitude and muscle force began to decline.…”
Section: Force Modelmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast, the rate of decline in maximal torque during 5 sets of 30 repetitions with maximal lengthening contractions with the ankle dorsiflexor muscles was greater for old adults (Baudry et al, 2007). (Dideriksen et al 2010b). One protocol (top) involved simulating contractions at five submaximal target forces (20,35,50,65, and 85% of MVC force) beyond the point in time when the muscle can achieve the target force and both EMG amplitude and muscle force began to decline.…”
Section: Force Modelmentioning
confidence: 85%
“…(1) repeated ramp contractions to 100% of the maximal voluntary contraction (MVC) force; (2) contractions sustained at two target forces (30 and 60% MVC force) for a similar force-time integral and then followed by ramp contractions; and (3) contractions sustained at five target forces (20-80% MVC force) for longer than the time to task failure (Dideriksen et al, 2010b). The association between EMG amplitude and muscle force varied across the protocols being bounded by the relation in the absence of the fatigue and the adjustments observed when the simulated contractions were sustained longer than task failure (Fig.…”
Section: Emg-force Relationmentioning
confidence: 99%
“…In recent studies, Dideriksen et al (2010aDideriksen et al ( , 2010b) tested a computational model that simulated changes in sEMG amplitude and muscle force during different fatigue protocols. They showed that during three different isometric protocols at different percentages of the maximal voluntary contraction (MVC), the relations between the amplitude and force were different depending on the fatigue protocol of the given study.…”
Section: Semg Amplitude-based Parametersmentioning
confidence: 99%
“…The thin solid lines represent the relations obtained from the various protocols. Reproduced with permission fromDideriksen et al (2010b).…”
mentioning
confidence: 98%